Knowledge acquisition for SMEs first entering developing economies: Evidence from Senegal - Sonia Ma. Suárez Ortega; Antonia Mercedes García-Cabrera; Gary Alan Knight (European Journal of Management and Business Economics (EJM&BE), 2016)
As developing economies have weak institutional environments, and these are highly distant from SMEs' home conditions in developed economies, those firms entering into developing economies should acquire new knowledge resources for a successful entry. In this paper, we analyze the type of knowledge required by SMEs to enter a foreign market, the alternative sources for acquiring that knowledge, and the specific challenges associated with the case of SMEs from developed economies in their first entry in developing economies. In our empirical work, we examined the specific case of Spanish SMEs entering Senegal as a first incursion in developing economies. This work shows evidence of usefulness to contribute to literature. Specifically, we found that the key knowledge is that which is specific to the target market, rather than the general knowledge about internationalization. In addition, we provide a matrix that summarizes the most appropriate sources to acquire each type of knowledge in the light of the main challenges identified: myopic managerial thinking, inflexible managers, absence of a culture of cooperation, and relevant knowledge embedded in local networks of the host market.
Keywords: O55; F23; M16; 650; Developing economies; Foreign market entry; Knowledge resources; Knowledge sources; Senegal; SMEs